Influência dos fatores pré-abate sobre a incidência de miopatias em frangos de corte - Abreu, Renata Alves Teixeira (2018)
Due to the improvement in the broiler performance of broiler chickens, the appearance of harmful muscle alterations has been observed in the industry. These are known as myopathies, affecting mainly the pectoral muscle of birds. These are Deep Pectoral Myopathy (MPP), wooden breast (WB), better known as "wooden breast" and white striping (WS). This study evaluated the incidence of myopathy within the industry and correlated with the number of heads of the lot, live weight, gender (male and female), lineage (A, B and C) and distance from farm to refrigerator. Data were collected from all batches slaughtered in a refrigerator located in northern Paraná, Brazil, from January to September 2017, and analyzed statistically to correlate with the incidence of myopathy. Statistical models of Poisson regression, quasi-Poisson regression and negative binomial regression were estimated. The number of heads per plot presented a linear relation with the number of birds with myopathy. There was a relative increase of 73.9% in the number of birds with myopathy in male chickens. For each kilometer from the farm to the slaughterhouse there was a relative increase of 0.06% in the number of birds with myopathy. There was a strong correlation between the number of birds with myopathy and live weight. Lineage A showed the greatest dispersion in the number of birds with myopathy, but there was no significant difference between the lines. In conclusion, the incidence of myopathy is of great concern and can affect more severely birds that come from more distant places, are males, with more heads and live weight in the lot.